Dėl socialinės istorijos lūžių Lietuvoje XIX-XX a. - Vyšniauskas, Arūnas (Lietuvos istorijos studijos, 1997)
The article deals with the main turning-points in the social history of Lithuania in the past two centuries. These social changes were determined by fundamental political changes in the system that were due to a new political geography in the Baltics and Eastern Europe. Russian and Soviet reforms had their effect on Lithuanian social history, as Russia determined the social development of conquered Lithuania. The spheres of influence from Russia, Poland, and Germany met in Lithuania. France, above all Napoleon, had had its influence on the social order; therefore, the study of the historical process in Lithuania can supply models of explanation for the historical process in general. The main interest lies not so much on the finding of patterns in which the autonomous systems develop, but rather on the interaction of the different social, political, and economic structures of religions, languages, and cultures.